Peran Guru Kelas Sebagai Pelaksana Bimbingan Dan Konseling Dalam Meningkatkan Prestasi Belajar Siswa Kelas IV SD Gedongan - Rismadona, Okswari Wahyuqi, Drs. Suwarno, SH, M.Pd (2017)
This study aims to determine the role of classroom teachers as implementers of guidance and counseling in improving student achievement Gedongan fourth grade. this type of research is qualitative research, data collection technique through interview, observation and documentation. Data analysis techniques in this study is an interactive analysis with the reduction step, presentation, and conclusion. Mechanical examination of the validity of data by using triangulation. This study aimed to describe, identify problems, identify solutions classroom teacher's role as executor of guidance and counseling in improving student achievement fourth grade N Gedongan. The results showed that the class teacher's role as executor of guidance and counseling in improving student achievement fourth grade N Gedongan a) Master class guide and pay attention to all the students carefully. b) The class teachers understand all the characteristics and abilities of each student. c) The class teachers always help students in solving problems, or difficulties he faced. d) Problems of students in the classroom and in the classroom learning process completed by the classroom teacher. e) In the implementation of guidance and counseling can be done classroom teachers currently teaching process, outside school hours, after school and during recess That depends circumstances. Constraints faced by classroom teachers a) The absence of a means of liaison between the classroom teacher and the tua.b) The lack of support and attention from parents in terms of student achievement. c) Lack of cooperation of parents in the preparation of teaching (Teaching and Learning). d) The level of ability and the development of different students. e) characteristics of students different because they have different family backgrounds. The solution to overcome the constraints of a classroom teacher) There must be a good relationship between teachers, students, and parents. b) The parents should always pay attention to the situation and the level of student achievement. c) If there is something less good or not immediately coordinate with classroom teachers, so that the problems can be solved. d) Provide guidance and direction to students. e) Provide liaison books to parents. f) Make props are practical but attractive. g) The learning process using the LCD. h) the environment outside the classroom to learn in order to not saturate in the classroom continues.